The stratigraphy of the Sterkfontein hominid deposit and its relationship to the underground cave system - Partridge, T C; Watt, I B (Bernard Price Institute for Palaeontological Research, 1991)
A programme of orientated core drilling was carried out during 1989 to elucidate stratigraphic relationships within the Sterkfontein Formation and to obtain a representative suite of samples for palaeomagnetic analysis. The cores have revealed that the hominid-bearing cave deposits occur as a continuous succession comprising 6 Members and extending to a maximum depth of about 30 m below present surface. Of these Member I (comprising a sterile, residual fill) and Member 3 are the most extensive. This sequence has been displaced vertically downwards within a zone of decalcification coinciding with the central part of the deposit. This zone has been the focus of recent deep excavations at the site. The results of the drilling, in conjunction with recent surveys of the underground cave system, confirm that a dolomite floor existed at an average depth of about 20 m at the time offirst cave filling. Subsequent cavern development down to depths in excess of 50 m caused the local collapse of some lower units of the Sterkfontein Formation and, as new openings developed to the surface, permitted the ingress of younger fills below the base of the hominid-bearing succession.
Keywords: cave deposit; South Africa; cradle of Humankind